Draft Genome Sequence of Bacillus toyonensis Strain GM18, Isolated from Agricultural Soil - Moreno Peña, Carlos J.; García García, Jorge Hugo; Hernández Vásquez, César Ignacio; Galán Wong, Luis Jesús; Pereyra Alférez, Benito; Stewart, Frank J. (American Society for Microbiology, 2021)
Bacillus toyonensis is a recently described species related to Bacillus cereus and Bacillus thuringiensis. The GM18 strain previously identified as B. thuringiensis is now classified as B. toyonensis based on the RNA 16S sequence and whole-genome average nucleotide identity. The genome analysis revealed the presence of insecticide, nematicide, and antitumoral proteins